CT ring sign imitating tumour, disclosed as multiple sclerosis by MRI: a case report. Issue 7 (July 1989) - Gütling, E; Landis, T
Abstract : A 21 year old woman with subacute onset of moderate left hemiparesis showed on CT scanning a left parietal ring shaped enhancing lesion indicative of tumour or abscess, while MRI revealed bilateral white matter lesions highly suggestive of MS. In none of the few similar cases reported was MRI available and most patients underwent biopsy or operation. The few reports of a CT-ring sign in MS are reviewed and the value of MRI in avoiding operation is stressed.